International Trade in Intermediate Inputs: The Case of the Automobile Industry - Markus Diehl (Kiel Institute of World Economics (IfW), 2001)
International trade statistics and input-output tables are analyzed in order to test the hypothesis that international production networks have become more relevant. The share of imported inputs in the gross output value of the motor vehicle industry has grown significantly during the last two decades. Moreover, some low-income countries have become strong exporters of automobile parts, but this trade is mainly regional rather than global. Detailed results are presented in case studies on four major producers (the United States, Japan, Germany and the UK).
Keywords: L63; F14; J31; 330; international trade; intermediate inputs; international outsourcing; Kraftfahrzeugteil; Außenhandel; Welt